The dog - Shaheen, safdar (Children publications; Karachi, 2008)
"The Dog by Quran Stories for Children" is a simple retelling of the Quranic story of the dog in the Cave of Ashab al-Kahf, teaching children lessons about loyalty, faith, and divine protection.